2011
DOI: 10.1159/000327219
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Cause of Gastrointestinal Bleeding: Duodenal Lipoma

Abstract: Common causes of chronic upper gastrointestinal bleeding include oesophageal varices, gastroduodenal ulcers and malignancy, and patients mostly present with iron deficiency type anaemia. We present the case of a 60-year-old lady who presented with iron deficiency anaemia and on investigation was found to have a large duodenal polyp requiring surgical excision. On histological examination, the polyp was revealed to be a lipoma. We review the recent literature and formulate a management plan for this rare entity. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…A study that involved 1200 duodenoscopies, reported only 2 patients with duodenal lipoma (7). They are usually asymptomatic and are discovered incidentally during endoscopy or surgery (1,2,6,8). Symptoms are generally related to the size of lipomas, and dyspepsia, epigastric fullness after meals, intestinal obstruction, or iron deficiency anemia due to occult or massive hemorrhage can be observed especially in duodenal lipomas larger than four centimeters (3,(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study that involved 1200 duodenoscopies, reported only 2 patients with duodenal lipoma (7). They are usually asymptomatic and are discovered incidentally during endoscopy or surgery (1,2,6,8). Symptoms are generally related to the size of lipomas, and dyspepsia, epigastric fullness after meals, intestinal obstruction, or iron deficiency anemia due to occult or massive hemorrhage can be observed especially in duodenal lipomas larger than four centimeters (3,(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…As the lipoma grows, the traction force of the intestinal content and peristaltic movement may cause erosion and ulceration of the mucosa, and can create a pedicle (4). Although endoscopic view supports the diagnosis, it is generally insufficient in making a definitive diagnosis since the tumor is submucosal, and forceps biopsies are generally inadequate for similar reasons (3,(6)(7)(8)(9). The definitive diagnosis is made after tumor excision and histopathologic examination (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations